2014
DOI: 10.1371/journal.pone.0090948
|View full text |Cite|
|
Sign up to set email alerts
|

Quantification of Pancreatic Cancer Proteome and Phosphorylome: Indicates Molecular Events Likely Contributing to Cancer and Activity of Drug Targets

Abstract: ObjectiveLC-MS/MS phospho-proteomics is an essential technology to help unravel the complex molecular events that lead to and propagate cancer. We have developed a global phospho-proteomic workflow to determine activity of signaling pathways and drug targets in pancreatic cancer tissue for clinical application.MethodsPeptides resulting from tryptic digestion of proteins extracted from frozen tissue of pancreatic ductal adenocarcinoma and background pancreas (n = 12), were labelled with tandem mass tags (TMT 8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 53 publications
0
40
0
Order By: Relevance
“…In case of multiple probes mapping to a single transcript, the probe with the most interquartile‐range variation across the samples, was retained in the analysis. Protein and phosphopeptide levels were assessed from 36 protein samples from the temporal cortex using SysQuant™ liquid chromatography tandem mass spectrometry (LC‐MS/MS) global proteomics (Proteome Sciences) as described 26, 27. LC‐MS/MS ‐based global proteomics identified 146,396 peptides mapping to 7516 unique proteins.…”
Section: Methodsmentioning
confidence: 99%
“…In case of multiple probes mapping to a single transcript, the probe with the most interquartile‐range variation across the samples, was retained in the analysis. Protein and phosphopeptide levels were assessed from 36 protein samples from the temporal cortex using SysQuant™ liquid chromatography tandem mass spectrometry (LC‐MS/MS) global proteomics (Proteome Sciences) as described 26, 27. LC‐MS/MS ‐based global proteomics identified 146,396 peptides mapping to 7516 unique proteins.…”
Section: Methodsmentioning
confidence: 99%
“…This novel approach has been used for in‐vitro studies, and was rarely applied to tissue samples. We recently developed a workflow called SysQuant that enables examination of the phosphorylation status of proteins extracted from frozen human tissue samples, by means of several phosphopeptide enrichment steps with immobilized metal affinity columns (IMAC) or titanium dioxide (TiO 2 ) . Crucially, SysQuant also measures protein expression by means of a non‐enrichment arm focusing on quantification of non‐phosphorylated peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Crucially, SysQuant also measures protein expression by means of a non‐enrichment arm focusing on quantification of non‐phosphorylated peptides. Our previous study on human pancreatic cancers revealed that 635 of 6543 phosphopeptides identified were modulated significantly between cancerous and background pancreatic tissue . The combined conventional proteomic and phosphoproteomic approach helped us to determine activated signalling pathways in pancreatic cancer tissue on a case‐by‐case basis …”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been carried out to explore molecular mechanisms underlying the development of PC, including genetic variations and environmental exposures . In recent years, with the wide applications of next‐generation sequencing and other high‐throughput technologies, genetic alternations in the genome, methylome, transcriptome, and proteome of PC cells have been intensively studied, which provide a systematic and unbiased view of variations at different levels . Genome‐wide sequencing approaches have identified a set of somatic mutations and genomic rearrangements that are associated with tumorigenesis of PC .…”
Section: Introductionmentioning
confidence: 99%